Bismuth Oxychloride Nanoplatelets by Breakdown Anodization. Issue 2 (31st October 2018) - Sopha, Hanna; Spotz, Zdenek; Michalicka, Jan; Hromadko, Ludek; Bulanek, Roman; Wagner, Tomas; Macak, Jan M.
Abstract: Herein, the synthesis of BiOCl nanoplatelets of various dimensions is demonstrated. These materials were prepared by anodic oxidation of Bi ingots in diluted HCl under dielectric breakdown conditions, triggered by a sufficiently high anodic field. Additionally, it is shown that the use of several other common diluted acids (HNO3, H2 SO4, lactic acid) resulted in the formation of various different nanostructures. The addition of NH4 F to the acidic electrolytes accelerated the growth rate resulting in bismuth‐based nanostructures with comparably smaller dimensions and an enormous volume expansion observed during the growth. On the other hand, the addition of lactic acid to the acidic electrolytes decelerated the oxide growth rate. The resulting nanostructures were characterized using SEM, XRD and TEM. BiOCl nanoplatelets received by anodization in 1 M HCl were successfully employed for the photocatalytic decomposition of methylene blue dye and showed a superior performance compared to commercially available BiOCl powder with a similar crystalline structure, confirming its potential as a visible light photocatalyst. Abstract : BiOCl nanoplatelets are produced by facile breakdown anodization of bismuth in diluted HCl electrolyte. The addition of lactic acid to the electrolyte decelerates the growth rate of the nanoplatelets while the addition of NH4 F or accelerates the growth rate. The nanoplatelets are single crystalline and show a superior photocatalytic behaviour compared to commercial BiOCl powder. Similarly, Bi2 O3 needles and Bi2 O3 cubes are produced in H2 SO4 and HNO3, respectively.